Non‐Random Patterns in the Distribution of NOR‐Bearing Chromosome Territories in Human Fibroblasts: A Network Model of Interactions. Issue 2 (February 2015) - Pliss, Artem; Fritz, Andrew J.; Stojkovic, Branislav; Ding, Hu; Mukherjee, Lopamudra; Bhattacharya, Sambit; Xu, Jinhui; Berezney, Ronald
<x xml:space="preserve">Abstract</x> We present a 3‐D mapping in WI38 human diploid fibroblast cells of chromosome territories (CT) 13, 14, 15, 21, and 22, which contain the nucleolar organizing regions (NOR) and participate in the formation of nucleoli. The nuclear radial positioning of NOR‐CT correlated with the size of chromosomes with smaller CT more interior. A high frequency of pairwise associations between NOR‐CT ranging from 52% (CT13–21) to 82% (CT15–21) was detected as well as a triplet arrangement of CT15–21‐22 (72%). The associations of homologous CT were significantly lower (24–36%). Moreover, singular contacts between CT13–14 or CT13–22 were found in the majority of cells, while CT13–15 or CT13–21 predominantly exhibited multiple interactions. In cells with multiple nucleoli, one of the nucleoli (termed "dominant") always associated with a higher number of CT. Moreover, certain CT pairs more frequently contributed to the same nucleolus than to others. This nonrandom pattern suggests that a large number of the NOR‐chromosomes are poised in close proximity during the postmitotic nucleolar recovery and through their NORs may contribute to the formation of the same nucleolus. A global data mining program termed the chromatic median determined the most probable interchromosomal arrangement of the entire NOR‐CT population. This interactive network model was significantly above randomized simulation and was composed of 13 connections among the NOR‐CT. We conclude that the NOR‐CT form a global interactive network in the cell nucleus that may be a fundamental feature for the regulation of nucleolar and other genomic functions. J. Cell. Physiol. 230: 427–439, 2015. © 2014 Wiley Periodicals, Inc.